Metformin and the Risk of Dementia in Type 2 Diabetes Patients - Chin-Hsiao, Tseng (Aging Dis, 2019)
This retrospective cohort study investigated dementia risk associated with metformin use in type 2 diabetes patients by using the reimbursement database of the Taiwan’s National Health Insurance. The patients had new-onset diabetes during 1999-2005 and were followed up until December 31, 2011. An unmatched cohort of 147,729 ever users and 15,676 never users of metformin were identified, and a matched-pair cohort of 15,676 ever users and 15,676 never users was created by propensity score (PS). Hazard ratios were estimated by Cox regression incorporated with the inverse probability of treatment weighting using PS. Results showed that in the unmatched cohort, 713 never users and 3943 ever users developed dementia with respective incidence of 1029.20 and 570.03 per 100,000 person-years. The overall hazard ratio was 0.550 (95% confidence interval: 0.508-0.596). The hazard ratio for the first (<27.0 months), second (27.0-58.1 months) and third (>58.1 months) tertile of cumulative duration of metformin therapy was 0.975 (0.893-1.066), 0.554 (0.506-0.607) and 0.286 (0.259-0.315), respectively. Analyses in the matched cohort showed an overall hazard ratio of 0.707 (0.632-0.791) and the hazard ratio for the respective tertile was 1.279 (1.100-1.488), 0.704 (0.598-0.829) and 0.387 (0.320-0.468). In conclusion, metformin use is associated with a reduced dementia risk.